2017
DOI: 10.4103/ijpsym.ijpsym_84_17
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Attitudes toward Patients with Psychiatric Illness among Postgraduate Indian Physicians

Abstract: Background: Due to paucity of psychiatrists in India, psychiatric patients often present to other doctors. We aimed to study nonpsychiatric residents’ attitude and stigma toward psychiatric patients. Methods: A total of 57 postgraduate trainees participated in a cross-sectional study in a tertiary hospital in New Delhi. Attitudes to psychiatric patients were assessed using the attitude to mental illness questionnaire (AMIQ) and the perceived stigma questionnaire. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
1
13
1
Order By: Relevance
“…Those with more clinical experience 63 or a family member or friend with mental illness 7,11 were more sympathetic towards the mentally ill. However, Chandramouleeswaran et al 55 found that personal contact with an individual with a psychiatric condition did not increase the positivity of mental illness attitudes.…”
Section: Sociodemographic Variables Associated With Attitudes Towards Mental Illnessmentioning
confidence: 97%
See 2 more Smart Citations
“…Those with more clinical experience 63 or a family member or friend with mental illness 7,11 were more sympathetic towards the mentally ill. However, Chandramouleeswaran et al 55 found that personal contact with an individual with a psychiatric condition did not increase the positivity of mental illness attitudes.…”
Section: Sociodemographic Variables Associated With Attitudes Towards Mental Illnessmentioning
confidence: 97%
“…11,54 Studies have shown that increased exposure to mentally ill people leads to more positive attitudes. 55,56,57 It is also likely that PS doctors are more open to advocating for their mentally ill patients because of the lesser demands and time constraints of their work as compared with state-employed doctors.…”
Section: Attitudes Towards Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, improved undergraduate training could lead to less stigmatization and better care for patients. [7] Furthermore, one of the most important impediments to progress in the development of mental health care is the stigma amongst health care providers. [8] According to Samari, Seow [9] perceived stigma amongst nurses towards mental illness and people with mental disorders can act as barriers to patients seeking treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[2,10] Furthermore, there were limited studies measuring attitudes and perceived stigma among university students toward mental illness. [7] However, there were no studies assessing stigma and attitudes of nursing students towards mental illness and comparing students who have received a psychiatric course and clinical placement with those who have not. [11] Also, the majority of the studies were considered to be of only moderate quality according to the JBI critical appraisal tool.…”
Section: Introductionmentioning
confidence: 99%